2018
DOI: 10.2991/itmr.7.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Knowledge Management on Employee Work Performance: Evidence from Saudi Arabia

Abstract: Knowledge Management (KM) has become critical in today's highly competitive, uncertain, and rapidly changing business environment. The objective of this study is to measure the effects of knowledge management processes (knowledge acquisition, knowledge sharing, knowledge creation and knowledge retention) and knowledge management approaches (social networks, codification and personalization) on job satisfaction and examines how they increase employees' work performance. A theoretical model based on KM processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 43 publications
3
33
0
1
Order By: Relevance
“…The findings indicated that the companies' management works hard to prevent staff from losing vital knowledge. The findings were in line with the discovery of Adman (2019), Alyoubi et al (2018), Kianto et al (2016), Najeeb (2018) and Pruzinsky & Mihalcova (2017). Also, the findings was inconsistent with the findings of Hussin and Mokhtar (2018), who found out that knowledge retention had no significant effect on competitive advantage.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings indicated that the companies' management works hard to prevent staff from losing vital knowledge. The findings were in line with the discovery of Adman (2019), Alyoubi et al (2018), Kianto et al (2016), Najeeb (2018) and Pruzinsky & Mihalcova (2017). Also, the findings was inconsistent with the findings of Hussin and Mokhtar (2018), who found out that knowledge retention had no significant effect on competitive advantage.…”
Section: Discussionsupporting
confidence: 91%
“…The findings from our study was in line with the result of Al-Nawafah (2019), Muchanji and Makokha (2018) and Agbim (2014). Contrarily, the finding was inconsistent with the discovery of Alyoubi, Hoque, Alharbi, Alyoubi and Almazmomi (2018), Hussin and Mokhtar (2018), Kianto et al (2016) and Pruzinsky and Mihalcova (2017). They found out in their studies that knowledge acquisition does not significantly influence companies' competitive advantage.…”
Section: Discussionmentioning
confidence: 67%
“…Knowledge management, known as KM, is the process of gaining experience, knowledge and expertise that results in new skills and drives new innovations, and creates good customer values. Because human knowledge, intelligence, and skills are secretly and individually catered, they are not easily captured and processed for the benefit of the organization [13].…”
Section: Table 3 T-test Resultsmentioning
confidence: 99%
“…The HTMT ratio for this study's four constructs is less than 0.9 (Table 5). Discriminant validity is achieved according to both methods applied, indicating that each construct is discriminately unique to the dimension that it intends to measure (Alyoubi et al, 2018). Structural model evaluation.…”
Section: Research Resultsmentioning
confidence: 99%